Madrasah Leadership and the Continuity of Qur'anic Education: An Analysis of the Excellent Qur'anic School Program - Fadeli Rhomadoni, Mohamad; Badrul Mudarris (Managere: Indonesian Journal of Educational Management, 2024)
This research examines the role of madrasah leadership in implementing and sustaining the Excellent Qur'anic School program at MI Nurul Islam Labruk Kidul. The study addresses the challenge many educational programs face, particularly in Islamic institutions, in maintaining long-term success and impact. Given the importance of Qur'anic education in shaping students' academic and moral development, understanding the factors contributing to such programs' sustainability is crucial. This study adopts a qualitative case study approach, utilizing observations, interviews, and documentation analysis to explore how leadership strategies influence the effectiveness and longevity of Qur'anic education programs. The findings reveal that the head of the madrasah plays a central role in the program's success through effective leadership, strategic planning, and continuous evaluation. The study concludes that sustainable educational programs depend not solely on teaching methods but also on the leadership vision and practices that guide them. These findings have broader implications for madrasahs and other educational institutions, providing valuable insights into how leadership can foster long-lasting and impactful educational programs.